Future of global retail : learning from China's retail revolution. - Nie, Winter; Greeven, Mark J.; Feng, Yunfei; Wang, James ([S.l.] : Routledge, 2022)
China's new retail revolution will completely transform how the world thinks about retail and digital innovation. But is the world ready yet? In this book, the authors share an insider's perspective on what is happening in China to reveal the future for global retail, and a clear framework to help you prepare. The book presents a number of real-world cases, based on interviews and first-hand consumer experience, to decode China's retail revolution so that you can understand what is happening and why, and what it means for the rest of the world. Crucially, the book identifies five critical stages in the development of new retail that global retail executives need to grasp now: lifestyle commerce, Online-Merge-Offline retail, social retail, livestream retail and invisible retail. To help the industry get ready for this new, China-inspired paradigm in retail, the authors present a practical and simple framework - a ten-year strategic roadmap for global retail executives, which we call the Beyond the Value Chain Model. China's new retail is not just about fashion, cosmetics, snacks, data-driven convenient stores and commercial live streaming. At a time when the world of retail is being upended, it offers inspirational lessons in innovation, purpose and agility for global executives across the entire retail spectrum.
OCLC-licensed vendor bibliographic record.
Keywords: Retail trade -- China -- Case studies; BUSINESS & ECONOMICS / Industries / Retailing; BUSINESS & ECONOMICS / Customer Service